Grape-vine Yellows - Aetiology, Epidemiology and Diagnosis - Magarey, P.A. (South African Journal of Enology and Viticulture, 2017)
Grape-vine Yellows comprise diseases with the same symptoms as Flavescence Doree (FD), a disease severe in Southern France and Italy, and caused by a procaryote. Other members include Bois Noir, Goldgelbe Vergilbung, and Australian Grape-vine Yellows. Yellows diseases have been observed in Europe, Australia, Israel, U.S.A. and Chile. Symptoms include yellow leaves which curl downward, and fall prematurely. Shoots are stunted and remain unlignified, and bunches shrivel and fall at flowering. Baco 22A, Jurancon blanc, Riesling and Chardonnay, are among the most susceptible cultivars. Scaphoideus titanus, the lealbopper vector of FD, is controlled by insecticides and loss from FD is now minimal. The other yellows diseases are of lesser importance and their aetiology is unresolved. Further investigation is needed to clarify the taxonomy of Grape-vine Yellows but the current diagnosis of yellows diseases of grape-vine is dependent on symptoms and at least one of several other features.